2017
DOI: 10.1103/physreve.96.033115
|View full text |Cite
|
Sign up to set email alerts
|

Smoothed particle hydrodynamics study of the roughness effect on contact angle and droplet flow

Abstract: We employ a pairwise force smoothed particle hydrodynamics (PF-SPH) model to simulate sessile and transient droplets on rough hydrophobic and hydrophilic surfaces. PF-SPH allows modeling of free-surface flows without discretizing the air phase, which is achieved by imposing the surface tension and dynamic contact angles with pairwise interaction forces. We use the PF-SPH model to study the effect of surface roughness and microscopic contact angle on the effective contact angle and droplet dynamics. In the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…In our previous work (Shigorina et al, 2017), we observed that, depending on its geometry and orientation, a “structured” surface roughness can accelerate or decelerate flow. In this work, we create random rough fracture surfaces with ζ = 0.75 and Δ = 10.0 and 20.0 mm, to approximate natural rough fracture surfaces.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous work (Shigorina et al, 2017), we observed that, depending on its geometry and orientation, a “structured” surface roughness can accelerate or decelerate flow. In this work, we create random rough fracture surfaces with ζ = 0.75 and Δ = 10.0 and 20.0 mm, to approximate natural rough fracture surfaces.…”
Section: Discussionmentioning
confidence: 78%
“…Prior to understanding the effect of soil physical properties on microbial activity, a thorough analysis of transport phenomena and their relevance is needed (Cai, Yu, Zou, & Mei, 2010; Shigorina, Kordilla, & Tartakovsky, 2017; Zhou, Helland, & Hatzignatiou, 2016; Zhu & Ma, 2018). Structural and topological characterization of the pore space is the first step in modeling fluid flow in soils.…”
Section: Physical Characterization Of Soilmentioning
confidence: 99%
“…The model is based on a PF-SPH discretization of the Navier-Stokes (NS) equation and can efficiently model flow through fractures or fracture networks and adequately recover all relevant flow dynamics, including the effects of free surface flows and surface tension (A. Kordilla J., 2013;Kordilla et al, 2017;Shigorina et al, 2017Shigorina et al, , 2019. However, in porous-fractured systems, the porous and/or permeable matrix represents an important storage compartment and influences flow dynamics within the highly permeable fractures.…”
Section: Manuscript Submitted To Water Resources Researchmentioning
confidence: 99%